2021
DOI: 10.1016/j.jogn.2020.09.159
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Quiet Time on the Auditory Environment of Infants in the NICU

Abstract: Participants: Sixty-six infants born at less than 38 weeks gestation who were between 32 and 40 weeks postmenstrual age. Setting: The auditory environments of infants in two level 3 NICUs within a pediatric hospital system in the Southeastern United States. Each NICU implemented quiet time for 4 hours per day. Methods: We assessed the auditory environment of the participants using Language Environmental Analysis technology. We used paired t tests to assess differences in the auditory environment during quiet v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…Moreover, previous research has shown that quiet time in hospitals, particularly in ICUs, provides many benefits, particularly in NICUs, where it is associated with more silence, fewer electronic sounds, and less talk than non-quiet time. Implementing quiet time decreases noise and exposure to electronic sounds in the NICU without sacrificing patient care [ 29 , 37 , 38 ]. Applebaum et al [ 39 ] found that most participants reported lower noise levels after quiet-time interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, previous research has shown that quiet time in hospitals, particularly in ICUs, provides many benefits, particularly in NICUs, where it is associated with more silence, fewer electronic sounds, and less talk than non-quiet time. Implementing quiet time decreases noise and exposure to electronic sounds in the NICU without sacrificing patient care [ 29 , 37 , 38 ]. Applebaum et al [ 39 ] found that most participants reported lower noise levels after quiet-time interventions.…”
Section: Discussionmentioning
confidence: 99%
“…During quiet time, measures should be implemented, including limiting conversations, eliminating environmental noise, and dimming lights [8]. Implementing quiet time protocols in the NICU results in positive outcomes for patients and healthcare professionals [29][30][31]. Quiet time contributes to healthier workplace environments [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…In the hospital setting, the census fluctuates and parents who received initial education were not present during the entire project. The PDSA (Plan-Do-Study-Act) method was utilized in the development and implementation of this pilot project 22…”
Section: Methodsmentioning
confidence: 99%
“…The PDSA (Plan-Do-Study-Act) method was utilized in the development and implementation of this pilot project. 22…”
Section: Project Overviewmentioning
confidence: 99%
“…The "quiet time protocol" or "quiet hour protocol" intervention includes a specific period consisting of 8-hour shifts during which light and sound are controllably reduced, and irritations at the patient's bedside are minimized (24,25). A protocol is designed to improve the environment by focusing on minimizing sound by including private rooms, educating staff about the negative effects of sound, keeping staff quiet, minimizing patient handling, turning down the alarm sounds, or setting them to vibration mode, using visual warning systems, responding immediately to the warning, building a toilet away from the baby's bed, and using plastic drawers instead of metal drawers (26). In the quiet time protocol, it is important to identify the source of the patient's stress as an environmental stimulus, prevent environmental stressors, and increase adaptation to the environment.…”
Section: Introductionmentioning
confidence: 99%